A study on the effect of amalgamation on the cost behavior of local public enterprises / Shoichiro Hosomi and Shohei Nagasawa. - Hosomi, Shoichiro; Nagasawa, Shohei (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
In this study, we focused on the amalgamations of local public enterprises and analyzed cost behavior before and after the amalgamations. From the perspective of cost management, it is possible that the amalgamations not only increase the burden of resource adjustment cost, but also make it more inefficient. For this reason, we classified management resources into tangible fixed assets, intangible fixed assets, and human resources to examine how each one affects the cost behavior of local public enterprises. As a result of our analysis, in local public enterprises, sticky costs after the amalgamation are stronger than before. It suggests that the larger management resources that resulted from the amalgamation increased the burden of the resource adjustment cost, which in turn strengthened sticky costs. Next, tangible fixed assets, which is the proxy index of material resources, has the effect of strengthening sticky costs after the amalgamation. Therefore, it is possible that the committed capacity cost increased even further with the amalgamation instead of improving the efficiency of the management. However, with respect to the hypothesis regarding intangible assets, we were unable to obtain significant results. Although various factors can be considered, since the types and nature of intangible fixed assets are diverse, it can be said that future studies such as analysis by each industry and ingenuity of analysis methods are necessary. On the other hand, we thought that human resources would act to strengthen sticky costs after the amalgamation, but this hypothesis was not supported. It is possible that, regarding human resources, the resource adjustment cost even decreases with amalgamations, weakening the influence of the costs.